Answer:
See Below.
Step-by-step explanation:
We want to verify the equation:
[tex]\displaystyle \frac{\cos y}{1-\sin y}=\frac{1+\sin y}{\cos y}[/tex]
On the left, we can multiply both layers by (1 + sin(y)):
[tex]\displaystyle \frac{\cos y}{1-\sin y}\left(\frac{1+\sin y}{1+\sin y}\right)=\frac{1+\sin y}{\cos y}[/tex]
Multiply:
[tex]\displaystyle \frac{\cos y(1+\sin y)}{1-\sin^2 y}=\frac{1+\sin y}{\cos y}[/tex]
From the Pythagorean Theorem, we know that sin²(y) + cos²(y) = 1. Hence, 1 - sin²(y) = cos²(y). Substitute:
[tex]\displaystyle \frac{\cos y(1+\sin y))}{\cos^2 y}=\frac{1+\sin y}{\cos y}[/tex]
Cancel:
[tex]\displaystyle \frac{1+\sin y}{\cos y}=\frac{1+\sin y}{\cos y}[/tex]
Hence proven.